PENGEMBANGAN MEDIA PEMBELAJARAN POLA BERBASIS ADOBE FLASH PADA MATA KULIAH MANAJEMEN TEKNOLOGI BUSANA - Sri Suparni (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
The purpose of this study is 1) to develop learning media product to create adobe flash-based patterns in fashion technology management courses, 2) know the feasibility of learning media to create adobe flash-based patterns in fashion technology management courses. This research is a type of research and development using 5 steps of developent according to thr Puslitjaknov Team which includes:analysis of the initial product being developed, developing products, expert validation and revision, small-scale field trials, and liited scale field trials.data collection techniques used were observation and questionnaire. The data analysis technique used is descriptive analysis technique. 1) The results of the analysis state that the developed media is a type of pattern using Adobe Flash, 2) The result of the expert of material was in very good category, the media expert was on very good category, the result of small scale in the category is very clear and result of a limited scale in the clear category as a medium for learning activities